2004
DOI: 10.1111/j.1365-2850.2003.00710.x
|View full text |Cite
|
Sign up to set email alerts
|

Seclusion: the inside story

Abstract: The objective of this study was to gain a better understanding of the seclusion room experiences of chronic psychiatric patients, the way in which they cope with their seclusion room experience, and the effect of seclusion on subsequent relations with care providers. A qualitative research design was used, in line with the procedure of Grounded Theory. Semi-structured interviews were held with seven chronic psychiatric outpatients whose seclusion took place at a certain remove in time. The transcriptions were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
95
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(100 citation statements)
references
References 11 publications
3
95
0
2
Order By: Relevance
“…Where consumers experience a loss of autonomy and trust and experience a sense of loneliness and isolation, the impact on the nursepatient relationship is likely to be negatively affected by the use of seclusion. These findings support those of similar research (Hoekstra et al, 2004;Holmes et al, 2004;Meehan et al, 2000;Wynaden et al, 2001).…”
supporting
confidence: 95%
See 1 more Smart Citation
“…Where consumers experience a loss of autonomy and trust and experience a sense of loneliness and isolation, the impact on the nursepatient relationship is likely to be negatively affected by the use of seclusion. These findings support those of similar research (Hoekstra et al, 2004;Holmes et al, 2004;Meehan et al, 2000;Wynaden et al, 2001).…”
supporting
confidence: 95%
“…The potential impact on the nurse-consumer relationship was described in a study from the Netherlands (Hoekstra, Lendemeijer, & Jansen, 2004). The responses from consumers reflected three major themes.…”
mentioning
confidence: 99%
“…Patients hospitalised more than once might be more familiar with the treatment system, adapted to their symptoms to some extent and had lowered their expectations of their living conditions and well-being (Kahneman et al 2004). Hoekstra et al (2004) concluded that the reasons for earlier secluded/restrained patients' positive experiences of coercion were associated with adaptation; learning to live with the experience rather than assimilation, active coping and control. Other factors during hospitalisation may also have impacted upon results: patients' recovery (Ristner et al 2011), psychoeducation received (Pitkänen et al 2011;Michalak et al 2005), therapeutic relationships between patients and nurses (Michalak et al 2005), or characteristics of the wards.…”
Section: Coerced Patients' Perceptions Of Their Overall Treatmentmentioning
confidence: 96%
“…Even though there are studies on patients' experiences of seclusion dating back to the 1970s and 1980s (Wadeson and Carpenter 1976;Binder and McCoy 1983;Soliday 1985;Hamill et al 1989;Mann et al 1993), interest in this theme has increased since about 2000 (Meehan et al 2000;Hoekstra et al 2004;Holmes et al 2004;Meehan et al 2004;Sørgaard 2004;Wynn 2005;Chien et al 2005;Stolker et al 2006;Steinert et al 2007;El-Badri and Mellsop 2008;Keski-Valkama et al 2010a;Kontio et al 2012).…”
Section: Patients' Perception Of Seclusion and Restraintmentioning
confidence: 96%
See 1 more Smart Citation